COMPARISON OF INCREASE IN INTRA-VAGINAL EJACULATORY LATENCY TIME (IELT) WITH FLUOXETINE AND PLACEBO IN PATIENTS OF PREMATURE EJACULATION - Muhammad Asif Gurmani; Muhammad Khalid; Muhammad Faizan (Journal of University Medical & Dental College, 2019)
OBJECTIVES: Compare the mean increase in Intra-vaginal ejaculation latency time (IELT) with the ﬂuoxetine and placebo in patients of premature ejaculation. STUDY DESIGN: Randomized Control Trial PLACE AND DURATION OF STUDY: Study was conducted at Department of urology, Teaching Hospital Dera Ghazi Khan, from 5th Jan 2017 to 4th Jan 2018 for period of one year. METHODOLOGY: Eighty patients were included to compare the mean increase in intravaginal ejaculatory latency time (IELT) with ﬂuoxetine and placebo in patients of premature ejaculation. The data was collected by a specially designed performa and the analyzed through SPSS-13. RESULTS: Majority of the patients in both groups were found between 41-51 years of age, in Group-A 35%(n=14) and 30%(n=13) in Group-B. Mean and standard deviation was recorded as 37.49±6.536 in Group-A and 35.69± 5.493 in Group-B. The pre-intervention intravaginal ejaculatory latency time (in seconds) was recorded in Group-A 48.17±2.66 while 48.75±2.78 in Group-B, which was found insigniﬁcant, while on post-intervention was found 176.20±6.61 in Group A while 65.22±2.64 in Group-B, p-value was 0.00, and we further recorded mean increase in intravaginal ejaculatory latency time (in seconds) also which shows mean 128.02±6.51 in Group-A and only 16.47±3.86 in Group-B and it was found highly signiﬁcant, p value was found 0.00 which is <0.05. CONCLUSION: Fluoxetine is an eﬀective drug for the treatment of premature ejaculation.